Radonas grunto ore ir patalpose Lietuvoje - Gasiūnas, Kęstutis; Mastauskas, Albinas; Morkūnas, Gendrutis (Journal of Civil Engineering and Management, 1998)
Concentrations of indoor and soil radon in Lithuania Uranium and its daughters including Ra-226 are naturally present in the Earth’s crust and other environmental bodies. During decay of Ra-226 radioactive noble gas radon is produced. This gas emanates to the atmosphere from solid matrixes containing Ra-226. It causes a special problem connected with the fact that radon accumulates in the closed spaces of buildings. Increased concentrations of radon indoors in many cases are the significant source of human exposure to ionizing radiation. Radon daughters having been deposited in the airways of human lungs are the source of alpha particles which irradiates the inner surface of airways. Since radiation quality of alpha radiation is high and small volumes of tissues are being irradiated, the influence of indoor radon as a source of ionizing radiation is significant. In order to forecast indoor radon concentrations and to take necessary remedial (in existing buildings) or prevention (in new buildings) measures, the main sources of indoor radon should be known in each country or geographical region. It may be soil, building materials, water and natural gas. It has been determined that the main source of indoor radon in Lithuania is soil. Permanent investigations of radionuclide content of building materials used or manufactured in Lithuania have not revealed any building materials with concentrations of naturally occurring radionuclides exceeding maximum permitted levels determined by the Lithuanian Hygienic Standards HN 40-1994. These investigations are performed by means of gamma spectrometry using the Ge spectrometer by Oxford after sample grinding and drying. A short review of radon risk mapping techniques used in Sweden, USA, Germany and Czech Republic is presented in paper. These techniques may be used for creation of similar technique in Lithuania with corrections connected with local geology. When determining radon risk mainly two parameters should be taken into account: radium content in soil (or radon content in soil air) which is associated with the type of soil and permeability of soil. The Lithuanian system of radon risk determination is not created yet because more detailed data on radon concentrations in soil air should be collected. Data from field measurements of radon concentrations in soil air and concentrations of naturally occurring radionuclides are presented. These measurements were carried out in some potentially important from the point of view of radon risk regions of Lithuania. Concentrations of Ra-226, Th-228 and K-40 in soil have been measured by gamma spectrometer GR-256 by Exploranium on the surface layer (up to 30 cm) of soil. Concentrations of radon in soil have been measured by MARKUS 10 in the depth of 70 cm. The measurements have been performed directly without sampling and sample preparation by digging the detector of Exploranium and pumping rod of MARKUS 10 in the investigated soil. The results indicate that there are some regions in Lithuania with radon concentrations in soil air exceeding 100 kBq/m3. Though radon risk depends on soil permeability these results show that these areas may be identified as areas of medium or even high radon risk. The system for classification of building sites in terms of indoor radon risk should be created in Lithuania in order to follow requirements of Lithuanian radiation protection standards and to keep below determined action levels of indoor radon- 400 Bq/m3 in existing buildings and 200 Bq/m3 in constructed ones. Results of indoor radon measurements are presented as well. The measurements have been performed in 400 randomly selected detached houses during heating season in two lowest permanently used rooms. Duration of one measurement exceeds 3 weeks. E-PERM electrets have been used for this type of measurements. The results show that the average concentration of indoor radon in Lithuania is 55 Bq/m3. In some cases these concentrations exceed the above-mentioned action levels and approach 2000 Bq/m. It shows that indoor radon problems exist in Lithuania as in many other countries. The average concentration of indoor radon in karst region is 125 Bq/m3. It shows that special attention should be paid to such regions because conditions for increased intake of radon to buildings may exist. Indoor radon is one of the main sources of exposure in Lithuania. In some cases it may be the essential source causing tens of milisieverts of annual effective dose. It shows that the problem of indoor radon is important in Lithuania. Article in Lithuanian. First Published Online: 26 Jul 2012